EMPOWERING TELEMEDICINE AS AN EFFORT TO ASSES KNOWLEDGE, ASTHMA SYMPTOMS CONTROL AND RISK FACTORS OF ASTHMATIC PATIENTS IN THE ERA OF COVID-19 PANDEMIC - Aditya Sri Listyoko; Susanthy Djajalaksana; Ngakan Putu Parsama Putra; Ungky Agus Setyawan; Caesar Ensang Timuda; Jimmy Akbar; Simon Petrus; Maria Kristiani; Ulfah Kartikasari; Yenny Widowati (Universitas Airlangga, 2022)
Introduction: Asthma is heterogenous disease characterized by chronic airway inflammation. COVID-19 pandemic has an impact on health services where telemedicine could provide alternative method to evaluate patient’s condition, reduce risk of infection and disease transmission. The aim of this study is to analysis knowledge, asthma symptoms control and risk factors among the asthmatic patients via telemedicine Methods: Data was obtained from telemedicine of 28 asthmatic patients in the context of community services. Inclusion criteria is stable asthmatic patients who conducted medical interview via videocall application. Cross sectional data were taken including demographic, knowledge of subjects, profile of subjects, and assessment of asthma symptoms control and assessment of poor outcomes. Data were analyzed descriptively and variables were analyzed using chi-square. Results: Subjects consisted of 28 stable asthmatic patients. The average of asthma onset was 17.96 years old. Clinically profile showed that 67.86% subjects were not routinely controlled, 64.29% had never performed pulmonary function test, 67.86% subjects didn’t know the level of asthma control symptoms. Evaluation based on GINA symptoms control only 39.29% were in good control condition, 35.71% were partially controlled and 25% in uncontrolled condition. Use of inhaler device recently or previously prescribed on 67.86% subjects. Evaluation of knowledge about asthma still unsatisfactory, 67.86% subjects didn’t know about their modifiable risk factors, 96.43% didn’t know about written action asthma plan, 60.71% didn’t know about asthma exercise. Self-medication was associated with poor asthma control (p=0,036) and knowledge about modifiable risk factors related to asthma symptoms control (p=0,041). Conclusion: Self-medication is related to uncontrolled asthma and knowledge of modifiable factors is related asthma symptoms control. It is important to educate the patient about the modifiable risk factors of asthma and how to manage it. Patient knowledge about their disease is still lacking, and there is a need for ongoing education to achieve good asthma control. Alternative intervention through telemedicine especially for continuing education and may therapeutic strategies can be performed as an effort to obtain well controlled asthma in community. Telemedicine, particularly in asthma management may benefit as an alternative approach of healthcare service in the context of pandemic era.